DEVELOPMENT OF DIGITALIZATION IN EU AND UKRAINE COUNTRIES - Okhrimenko , B.O. (The actual problems of regional economy development, 2021)
The rapid development of information and communication technologies in recent decades has led to significant changes in the development of the world economy. These modern technologies permeate all spheres of human life, opening new opportunities for achieving socio-economic development. Digitalization of the economy and society is one of the most dynamic changes of our time, which opens new opportunities in creating business models and at the same time brings uncertainty and various threats associated, in particular, with the social effects of automation of production processes. Digitalization, as a continuous process of convergence of the real and virtual world, is becoming a major driver of innovation and change in most sectors of the economy. The article is aimed at comparing the development of digitalization in the countries of the European Union and Ukraine. The theoretical and methodological basis of the study is the dialectical theory of cognition and a systematic approach to the study of economic phenomena and processes, the theoretical positions of domestic and foreign scientists on the digitalization of society. Scientific research was conducted using the following methods: monographic, dialectical, system-analytical, abstract-logical, comparative, etc. It is established that the level of digitalization of the country is assessed by a set of factors that are part of the integrated indicator - the Digital Economy and Society index. It is determined by analyzing key indicators: broadband, human capital, Internet use, digital integration, and digital government services. The analysis shows that the level of digitalization in Ukraine today is at an initial level and is much lower than in the European Union. The Digital Economy and Society index in EU-27 in recent years is at the level of 0.48, and in Ukraine - only 0.18. The main reasons for the low level of digitalization of our country are identified; economic crisis, underdeveloped infrastructure in this area, low level of education and insufficient level of knowledge in the field of digitalization, imperfection of legislative and institutional support, etc. However, it is established that Ukraine has significant potential for the development of digitalization.